PENGEMBANGAN HANDOUT BERBASIS GAMBAR DAN BERKARAKTER PADA MATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN UNTUK TINGKAT SMP - -, Nuraini - (STKIP PGRI Sumbar, 2014)
Assignment of a teacher was not only teaching in front of class, but a teacher has to able to make learning material for their students so it can improve students motivation. Based on observation in SMPN 2 Rao Kabupaten Pasaman. Learning material used in learning process was text book. The condition of text book is self was broken and it was not enough. Solution of the problem, one of learning material that can be used be the teacher was handout of picture and character. The background of this research was to know validity and practicality of handout based on picture and character for material structure and function of plants system. This research was a development research that used 4-D models. Handout development based on picture and character for material structure and function of plants system was valid and praktis.